Spatio-temporal Variation of Hydrological Drought in the Indo-Gangetic Plains - Khanna, Manoj; Kumar, Mukesh; Rani, Rekha; Pathak, Himanshu (Journal of Agricultural Engineering, 2018)
The Indo-Gangetic plains (IGP) encompass a large alluvial track consisting of multi-tier aquifer system. Due to stride developmental activities and intensification of agriculture with higher irrigation water requirement, shallow groundwater regime is getting depleted causing hydrological drought. Spatio-temporal variation of seasonal drought pattern and drought severity in the IGP region was analysed for the period of 2005-2009, using Standardized water level index (SWI) with topo to raster methods of interpolation in geographic information system (GIS). Analysis of hydrological drought indicated that 40-60 % area in the IGP was affected by mild hydrological drought, whereas 2-7 % of the area was affected by extreme hydrological drought because of excessive and indiscriminate groundwater pumping leading to decline in groundwater level. SWI categories were correlated with the irrigation activity for better irrigation planning. Irrigation planning for the IGP was suggested for different SWI drought categories.